A ANALISIS BREAK EVEN POINT (BEP) USAHA PENGASAPAN “IKAN CAKALANG ASAP” DI PROVINSI SULAWESI UTARA - Ira Primalasari (JURNAL CITRA AGRI TAMA, 2022)
The purpose of this study was to determine the Break Even Point the smoked skipjack business in North Sulawesi. This research is located in 6 places in the City and Regency of North Sulawesi Province with a total of 81 respondents. Date analysis in this study use a quantitative descriptive approach and Break Even Point analysis. The results showed that the Unit Break Even Point value was 312 kg. this means that smoked skipjack fish craftsmen can maintain their profit level in a minimum production amount of 312 kg. if it is less than the BEP unit, smoked skipjack fish craftsmen will suffer losses. This is also related to the selling price of smoked skipjack fish of IDR 62, 120 per kg. smoked skipjack fish craftsmen will not experience profit or loss when the amount of smoked skipjack production produced is only 312 kg. the value of the Break Even Point in the processing of smoked skipjack is IDR 19,395,909,-. This means that when the selling price of smoked skipjack per kg is IDR 62, 120 and the total production is 5,755 kg, then the smoked skipjack fish processing business will experience neither profit nor loss Key words : Smoked Skipjack, Break Even Point